2019
DOI: 10.1016/j.ijrobp.2019.06.2145
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio Predict Poor Survival in Rectal Cancer Patients Receiving Neoadjuvant Concurrent Chemoradiotherapy

Abstract: was calculated for all the patients from the two groups. The patient acute hematologic toxicity (e.g. patient with symptoms of leukopenia, neutropenia, anemia, or thrombocytopenia) was recorded according to RTOG scoring scale. Independent sample t test were applied for the dose-volume parameters, and card square analysis for clinical parameters. Results: In terms of the OAR dose-volume parameters, the V 5 wV 35 and D mean for the pelvic bone, left femoral head and the right femoral head significantly (p<0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In terms of survival rate, many studies have investigated whether pretreatment serologic markers, such as PLR and NLR, are associated with long-term oncologic survival as well as pCR in rectal cancer patients who underwent neoadjuvant CRT. A retrospective study by Ke et al [9] revealed that a pre-CRT elevated PLR ( > 188) was an independent prognostic factor for poor DFS, but not for OS, and that a pre-CRT elevated NLR ( > 3.5) was an independent prognostic factor for both poor DFS and OS. Zhang et al [28] reported that a high NLR ( ≥ 2.3) was associated with unfavorable OS and DFS, and they also reported that NLR was the most effective prognostic marker according to time-dependent ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of survival rate, many studies have investigated whether pretreatment serologic markers, such as PLR and NLR, are associated with long-term oncologic survival as well as pCR in rectal cancer patients who underwent neoadjuvant CRT. A retrospective study by Ke et al [9] revealed that a pre-CRT elevated PLR ( > 188) was an independent prognostic factor for poor DFS, but not for OS, and that a pre-CRT elevated NLR ( > 3.5) was an independent prognostic factor for both poor DFS and OS. Zhang et al [28] reported that a high NLR ( ≥ 2.3) was associated with unfavorable OS and DFS, and they also reported that NLR was the most effective prognostic marker according to time-dependent ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-to-lymphocyte (PLR) and neutrophil-to-lymphocyte (NLR) ratios have been widely used as prognostic tools in various malignancies, based on the theory that platelets and neutrophils are pro-tumorigenic factors and lymphocytes are protective factors against tumors [7,8]. Some studies have reported that elevated PLR and NLR can reflect poor oncologic outcomes as well as response to neoadjuvant CRT in rectal cancer patients [9,10]. However, there are still debates about the prognostic effect of PLR and NLR for locally advanced rectal cancer cases because of existing contradictory results [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer is the third most common malignancy and ranks second among cancer deaths [ 1 ]. Rectal cancer accounts for nearly one-third of all colorectal cancers, and almost half of them are diagnosed with locally advanced stage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] These tests are inexpensive and can be readily performed in daily oncologic practice. However, although some studies showed significant correlation between low LMR and high PLR and poor survival outcomes of rectal cancer, [12][13][14][15][16][17] others failed to replicate these results. [18][19][20][21][22][23] These discrepancies may relate, in part, to differences in treatment modalities and tumor characteristics.…”
mentioning
confidence: 99%